AN INVENTORY POLICY FOR CRITICAL COMPONENTS IN BOTTLE WASHER MACHINES AT PT SINAR SOSRO, FACTORY AT GIANYAR-BALI - Ayu Putu Sintia Dewi, Sang
PT. Sinar Sosro is one of the industries engaged in the processing of packaged tea leaves which have several flavors. This research will focus on the policy of controlling the inventory of critical engine components on line 1 of PT. Sinar Sosro, especially in bottle washing machines. The problem that occurs is related to inventory control of this critical component, namely the frequent shortages when machine components are needed. This deficiency is caused by PT. Sinar Sosro, the Gianyar factory, does not have a definite system in controlling its engine components. So they will only order when the stock of components is out of stock in the warehouse. The proposed system improvement to overcome these problems is to use an ordering system by applying an ordering policy model. Ordering policy is an inventory control model that accommodates the interrelationships between goods in the ordering system. This study has 4 stages, namely the first stage is the selection of critical components from the bottle washer machine that comes from one supplier then data collection related to the selected critical components is carried out which will be used as input for policy calculations The third stage is calculating the parameters (S, c, s) in accordance with the policies that can be ordered. The last stage is a comparison between the proposal policy and the company's existing policy based on the existing parameters. This research was conducted on 8 critical components of bottle washing machines ordered from the same supplier to produce optimal inventory levels using policy calculations. The comparison obtained is that by using the ordering policy, the company can save 5.3% of the total inventory cost when compared to the company's system. In addition, the Company will not experience a shortage of components in the warehouse so that the company will not suffer losses due to too long downtime.